The Conditions of Creation and Prospects of Weather Derivatives Development on the Domestic Market - Piotr Binkowski (Contemporary Economics)
Analysing the possibility of creations and prospects of weather derivatives development on the domestic market the first of all should be identify the business areas that are strongly exposed for weather risk, which are: energy, agricultural, building and transportation. The specificity of the Polish climate is the high volatility of the major weather factors like temperature or precipitations. Similar to other European countries where weather derivatives markets already exist (e.g.: Germany, France, and United Kingdom). Having in mind dynamic grow of companies with regards to management processes, used technologies and marketing strategies, the exposure for weather risk is getting higher. Therefore, there is a strong pressure for creation of mechanisms and instruments that will allow reducing that kind of risks. Currently in Poland there are no conditions for development of weather derivatives market due to lack of demand. That situation is caused by low level of awareness regarding to possibilities of reducing weather risks. Within a few years the demand for such the instruments will appear ñ together with growing awareness. Once the demand for weather derivative will appear, the existing infrastructure of financial sector is ready for its implementation. Of course it is hard to say what will be the direction of whether derivatives grow on the domestic financial market but taking into consideration its dynamic grow and strong correlations with global markets, there is a small probability that weather derivatives will not appear on the Polish market ñ it is only the matter of time.